IMPLEMENTASI PENDIDIKAN AGAMA ISLAM YANG BERWAWASAN LINGKUNGAN HIDUP DAN BUDAYA SEKOLAH DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 4 REJANG LEBONG - Sri Astuti (UIN Fatmawati Sukarno Bengkulu, 2019)
This study aims to : 1. Describe the impementation of environmental Islamic Education anjd school culture at SMP Negeri 4 of Rejang Lebong, 2. Describe the concept of Islamic religious education that is environmentally sound and school culture applied at SMP Negeri 4 of Rejang Lebong, 3. Describe the inhibiting factors and driving dactors in realizing a school environment that is environmentally sound and school culture. In the context of this study the variable is the implementation of envinronmental Islamic religious education and the school culture in creating a atmosphere school environment. The method of this research is qualitative description using the analysis of triregulation. Research consists of three variables, namely ; Imlementation of Islamic Education, Environment and School Culture. The results of the study concluded that in the material of Islamic Education there are discussions related to education contained environment and School Culture. The results of the study concluded that in the material of Islamic Education there are discussions related to education contained environmental and the school culture materials. The material intended is all clean living to be comfottable, halal and haram food, the beauty of being being together with congregational prayers, and the hadith about cleanliness. The types of activities that are environmentally sound that are applied at SMP Negeri 4 of Rejang Lebong are waste management, tree protection, drainage and biopori, ornamental plants school, health health businesses (UKS), and healthy canteens. While the school culture applied at the school is Culture, greetings, meditation, smile polite, and polite (5S), discipline, responsibility, religious, and honest